Experimental transmission of Tomato yellow leaf curl virus (TYLCV) by Bemisia tabaci (Aleyrodidae) to solanáceas - CHIRINOS, DORYS T.; GÜERERE, PASCUAL; GERAUD-POUEY, FRANCIS; ROMAY, GUSTAVO; SANTANA, MARÍA A.; BASTIDAS, LISETH (Revista Colombiana de Entomología, 2009)
Between December 2006 and May 2007 the transmission of an isolate of the Tomato yellow leaf curl virus (TYLCV) by Bemisia tabaci to several cultivated and wild solanaceous species was studied to determine their role as possible hosts of this virus. Plants of Solanum lycopersicum L., S. melongena L., S. hirtum Vahl, S. sisymbriifolium Lam., Datura stramonium L., D. inoxia Mill. Physalis angulata L., and P. ixocarpa Brot. were individually exposed during 48 h to B. tabaci adults reared on infected tomato plants. Control plants belonged to the same species but these were exposed to adults reared on virus free cotton plants. Thereafter, the plants were maintained inside B. tabaci test cages and observations were made to detect symptoms up to 30 days post exposure to the vector. Then foliar apex samples were taken for virus determinations through PCR. Symptoms of TYLCV infection were only observed on S. lycopersicum and D. stramonium at days 12 and 13, respectively, reaching 100% of the plants evaluated. TYLCV infection was corroborated through PCR. In the other plants exposed to infected adults, besides not showing symptoms, the virus was not detected by PCR. Additional observations it was detected that the insect did not form colonies on D. inoxia and S. sisymbriifolium. These results contribute information about the host range of this isolate of TYLCV in Venezuela, where this virus was recently reported for the first time in South America.